Taxonomic affinities of the putative titanosaurs from the Late Jurassic Tendaguru Formation of Tanzania: phylogenetic and biogeographic implications for eusauropod dinosaur evolution. Issue 3 (25th January 2019) - Mannion, Philip D; Upchurch, Paul; Schwarz, Daniela; Wings, Oliver
Abstract: The Late Jurassic Tendaguru Formation of Tanzania, southeastern Africa, records a rich sauropod fauna, including the diplodocoids Dicraeosaurus and Tornieria, and the brachiosaurid titanosauriform Giraffatitan . However, the taxonomic affinities of other sympatric sauropod taxa are poorly understood. Here, we critically reassess and redescribe these problematic taxa, and present the largest phylogenetic analysis for sauropods (117 taxa scored for 542 characters) to explore their placement in Eusauropoda. Janenschia robusta has played a prominent role in discussions of titanosaur origins, with various authors referring at least some remains to Titanosauria, a clade otherwise known only from the Cretaceous. Redescription of the holotype of Janenschia, and all referable remains, supports its validity and placement as a non-neosauropod eusauropod. It forms a clade with Haestasaurus from the earliest Cretaceous of the UK, and the Middle/Late Jurassic Chinese sauropod Bellusaurus . Phylogenetic analysis and CT scans of the internal pneumatic tissue structure of Australodocus bohetii tentatively support a non-titanosaurian somphospondylan identification, making it the only known pre-Cretaceous representative of that clade. New information on the internal pneumatic tissue structure of the dorsal vertebrae of the enigmatic Tendaguria tanzaniensis, coupled with a full redescription, results in its novel placement as a turiasaur. Tendaguria is the sister taxon of Moabosaurus, from the Early Cretaceous of North America, and is the first turiasaur recognized from Gondwana. A previously referred caudal sequence cannot be assigned to Janenschia and displays several features that indicate a close relationship with Middle–Late Jurassic East Asian mamenchisaurids. It can be diagnosed by six autapomorphies, so we erect the new taxon Wamweracaudia keranjei gen. et sp. nov. The presence of a mamenchisaurid in the Late Jurassic of southern Gondwana indicates an earlier and more widespread diversification of this clade than previously realized, prior to the geographic isolation of East Asia. Our revised phylogenetic dataset sheds light on the evolutionary history of Eusauropoda, including supporting a basal diplodocoid placement for Haplocanthosaurus, and elucidating the interrelationships of rebbachisaurids. The Tendaguru Formation shares representatives of nearly all sauropod lineages with Middle Jurassic–earliest Cretaceous global faunas, but displays a greater range of diversity than any of those faunas considered individually. Biogeographic analysis indicates that the Tendaguru sauropod fauna was assembled as a result of three main phenomena during the late Early and/or Middle Jurassic: (1) invasions from Euramerica (brachiosaurids, turiasaurs); (2) endemism in west Gondwana (dicraeosaurids, diplodocids); and (3) regional extinctions that restricted the ranges of once widespread groups (mamenchisaurids, the Janenschia lineage). Multiple dispersals across the Central Gondwanan Desert are required to explain the distributions of Jurassic sauropods, suggesting that this geographic feature was at most a filter barrier that became easier to cross during the late Middle Jurassic.